The Influence of the Role of Agricultural Extension Agents on the Socio-Economic Conditions of Farmers in "Ngawi" Farmers Groups in Kumpai Batu Atas Village, South Arut District, West Kotawaringin Regency - shofiyah shofiyah; Risca Permatasari; Aminatun Aminatun (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2019)
This research was carried out in Kumpai Batu Atas Village, South Arut District, Kotawaringin Barat Regency. This study aims to determine the influence of the role of agricultural extension agents on the socio-economic conditions of farmers. Data analysis method uses Likert scale, descriptive analysis, multiple linear regression analysis, f-test and determination coefficient. The data collected in this study are primary data and secondary data.The socio-economic conditions of farmers in "ngawi" farmer groups consist of the age of farmers 30-40 years (12%), 41-50 years (24%), 51-60 years (48%); education consists of elementary school (64%), junior high school (32%), S1 (4%); income level range <Rp. 1,500,000 (34%), Rp. 1,500,000 - Rp. 2,500,000 (64%),> Rp. 2,500,000 - Rp. 3,000,000 (12%) and the work of the farmer respondent all (100%) earns a living as farmer.                 The results showed the hypothesis testing together had a fcount of 0.087 smaller than the value of ftabel of 3.44 which means that Ha was rejected and H0 was accepted, this indicates that the independent variable includes the factors of instructor as educator, facilitator and supervisor together- the same does not affect the dependent variable, namely the socio-economic conditions of the farmers. Based on the results of multiple linear regression analysis obtained equation Y = 1.64 + 0.35 X1 + 0.13 X2 + 0.05 X3 + e which indicates a positive influence between the instructor factors as educators, facilitators and supervisors on the social economic conditions of farmers. The coefficient of determination (R2) obtained shows that 11.1% of socioeconomic conditions can be influenced by the extension factor as an educator, facilitator and supervisor.